Posterior reversible encephalopathy syndrome following post-streptococcal glomerulonephritis (Bangladesh Journal of Medical Science, 2013)
Posterior reversible encephalopathy syndrome (PRES) comprises a unique pattern of brain vasogenic edema that is seen in the setting of a neurotoxic status. Besides many etiologies have been already associated with PRES development, such as chronic renal disease, use of chemotherapy agents and inflammatory conditions, the imaging features are very suggestive and helpful for an appropriate diagnosis. We report here a case of PRES secondary to post-streptococcal glomerulonephritis (PSGN), which evolved successfully after clinical management. An 11-year-old boy was admitted with a typical history and findings of PSGN, associated with sensory alterations, headache and recent tonic-clonic seizure. Computed tomography (CT) scan of the head has revealed bilateral and symmetric hypodense areas, remarkably located at posterior cerebral regions, indicating PRES. Patient received support therapy with diuretics, and antibiotics prescription after discharge. At ambulatory follow-ups, the patient remains asymptomatic, with complete clinical and radiological improvement.Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 341-343 DOI: http://dx.doi.org/10.3329/bjms.v12i3.13323